3D Flower‐Like Carbon Spheres with Hierarchical Pore Structure: An Efficient Asphaltene‐Based Metal‐Free Catalyst for ORR. Issue 30 (9th September 2022) - Qin, Fangfang; Zuo, Pingping; Li, Na; Qu, Shijie; Shen, Wenzhong
Abstract: 3D carbon superstructures assembled from low‐dimensional segments can inherit the specific properties of their building blocks and gain certain unconventional advantages that make them attractive candidates for electrocatalysts. Furthermore, hierarchical pores and nitrogen doping are effective strategies to enhance carbon‐based metal‐free catalysts. Based on this, 3D flower‐like carbon spheres with a micro‐meso‐macroporous hierarchical pore structure constructed from 2D porous nanosheets are designed and developed using asphaltene as carbon precursor in this work. The high specific surface area and hierarchical pore structure of the prepared catalyst maximize exposure of the active sites and facilitate the penetration of electrolytes and the rapid transport of ions and O2, thus improving its oxygen reduction reaction (ORR) activity. It shows good ORR properties in both acid and alkaline electrolyte with E on of 0.77 and 0.98 V, and E 1/2 of 0.60 and 0.833 V, respectively. When the catalyst is assembled into zinc–air battery, it shows a specific capacity of 797 mAh g –1 and an open‐circuit voltage of 1.544 V. Furthermore, the assembled battery displays good cyclic stability with stable charge and discharge exceeding 150 h at 5 mA cm –2 . Abstract : N‐doped 3D flower‐like carbon spheres assembled by nanosheets is constructed via hydrothermal and carbonization processes; it shows efficient ORR performance in both acidic and alkaline electrolyte as a metal‐free catalyst.